2005
DOI: 10.1002/ange.200500353
|View full text |Cite
|
Sign up to set email alerts
|

An Onion Phase in Salt‐Free Zero‐Charged Catanionic Surfactant Solutions

Abstract: Mixtures of cationic and anionic (catanionic) single-chain surfactants can readily form bilayers in aqueous solutions, [1] in which uni-and multilamellar onion phases (the so-called vesicle phase) are often observed to be in equilibrium. [2] Since vesicles represent simple model systems for biological membranes and have practical applications (for example, for controlled drug or DNA release), [3] investigations of vesicle phases are of considerable interest in different areas, including surfactants, materials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 18 publications
7
25
0
Order By: Relevance
“…In previous studies, all samples were found to exhibit shear-thinning behavior over the studied shear-rate range, which was typical for L a -phase solutions. [27,32,33] When c DEHPA was within the range 300-320 mmol L À1 , we observed partial shear-thickening behavior within the shear-rate range of 50-100 s À1 , for which the planar lamellar structure was confirmed by the above FF-TEM images. It was previously reported that vesicles could be prepared from the classical planar lamellar phase through shearing, with an improvement of viscosity.…”
Section: Rheological Propertiessupporting
confidence: 61%
See 3 more Smart Citations
“…In previous studies, all samples were found to exhibit shear-thinning behavior over the studied shear-rate range, which was typical for L a -phase solutions. [27,32,33] When c DEHPA was within the range 300-320 mmol L À1 , we observed partial shear-thickening behavior within the shear-rate range of 50-100 s À1 , for which the planar lamellar structure was confirmed by the above FF-TEM images. It was previously reported that vesicles could be prepared from the classical planar lamellar phase through shearing, with an improvement of viscosity.…”
Section: Rheological Propertiessupporting
confidence: 61%
“…Freeze‐fracture (FF) TEM is a powerful tool that can provide direct information on self‐assembled surfactant structures in their hydrated state 27. The microstructure transition in the lamellar phase at c L ‐Arg =300 mmol L −1 with different c DEHPA values is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth conducting further studies, with the aim of exploring the potential of these responsive, compartmentalized membranes as functional coatings for food preservation, hierarchical nanoreactors, and transport membranes and to extend the deposition process to different substrates. The method presented in this work is not restricted to polymer/surfactant mixtures, and we expect that similar multilayered coatings can be prepared applying an analogous rapid, single-step procedure to a large variety of spontaneously assembled, hybrid, layered systems in bulk solution, such as: catanionic 58,59 , surfactant/polyoxometalates 60 , fullerene/polyoxometalates 61 , and DNA/lipid multilayer 62,63 vesicles.…”
Section: Discussionmentioning
confidence: 99%